2001
DOI: 10.1111/j.1365-2621.2001.tb16139.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Lentil Cooking Time Using Micronization: Comparison of 2 Micronization Temperatures

Abstract: Laird No. 1 lentils micronized (high-intensity infrared heat) to give internal temperatures of 138 and 170 °C were compared to unprocessed lentils stored at room temperature. Micronized lentils, which had been tempered to 33% moisture for 16 h, required less force to compress after cooking and contained increased levels of gelatinized starch and pectic substances but decreased levels of soluble protein, phytic acid, and neutral detergent fiber compared to the unprocessed lentils. Cell walls in the micronized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 19 publications
9
49
0
Order By: Relevance
“…Wrinkled seed coats were seen in the seeds tempered to 16 and 23% moisture and micronized to 115 and 130°C temperatures. Using green lentil with seed coat, Arntfield et al (2001) have also reported that red, less yellow and darker seeds were produced as the micronizing temperature increased from 138 to 170°C.…”
Section: Micronization Treatment Of Lentil Seedsmentioning
confidence: 93%
“…Wrinkled seed coats were seen in the seeds tempered to 16 and 23% moisture and micronized to 115 and 130°C temperatures. Using green lentil with seed coat, Arntfield et al (2001) have also reported that red, less yellow and darker seeds were produced as the micronizing temperature increased from 138 to 170°C.…”
Section: Micronization Treatment Of Lentil Seedsmentioning
confidence: 93%
“…decreasing the cooking time of lentils (Cenkowski and Sosulski,I99l;Arntfield et al, 2001), split peas (Cenkowski and Sosulski, 1998) and chickpeas (Sarantinos and Black, 1996); reducing bitterness in raw pea protein (McCurdy, 1992); inactivating lipoxygenase in soybeans (Van Zuilichem et al, 1986) and keeping protein denaturation to a minimum which improves brewing performance (South, 1992). Nutritional properlies have also been improved by the reduction of phytic acid and phenolic compounds in lentils (Zhao, 2000;Arntfield et al, 2001), the increase of invitro protein digestibility and available lysine in soybean milk (Metussin et aL., 1992), the increase in 7o soluble dietary fibre and decrease in insoluble dietary fibre in lentils (Zhao,2000), and the decrease in protein solubility (which increases digestibility due to the higher protein denaturation) (Amtfield et al, 200L,Zheng et al, 1998).…”
Section: Results Of Consumer Testing On Existing Commercially Availabmentioning
confidence: 99%
“…Nutritional properlies have also been improved by the reduction of phytic acid and phenolic compounds in lentils (Zhao, 2000;Arntfield et al, 2001), the increase of invitro protein digestibility and available lysine in soybean milk (Metussin et aL., 1992), the increase in 7o soluble dietary fibre and decrease in insoluble dietary fibre in lentils (Zhao,2000), and the decrease in protein solubility (which increases digestibility due to the higher protein denaturation) (Amtfield et al, 200L,Zheng et al, 1998). Microbiological quality has also been improved by the reduction of mold formation in chickpeas (Sarantinos and Black, 1996).…”
Section: Results Of Consumer Testing On Existing Commercially Availabmentioning
confidence: 99%
“…Arntfield et al [4] compared the impact of processing at two micronization temperatures (138 and 170°C) on the Laird lentils quality characteristics. Lentils (33 %, d.b) micronized (170 s) to attain an internal temperature of 138 and 170°C required less compression force (63 and 55 %).…”
Section: Micronization Of Legumesmentioning
confidence: 99%
“…Both surface (a, c, e) and cross sections (b, d, f) have been examined (reprinted from Arntfield et al[4], copyright year: 2015 with permission from John Wiley and Sons)…”
mentioning
confidence: 99%